HUBUNGAN ANTARA PRODUSEN DAN KONSUMEN: SEBUAH TINJAUAN ETIS - Acin, Mayong Andreas (MABIS, 2012)
The purpose of this article is to provide an ethical foundation for relationship marketing using a virtue ethics approach. A phrase: âThe customer is a kingâ means the customer is essential to the welfare of the business. On one hand, buyer and seller have a shared interest in âdoing the dealâ. They want to do business with each other, and both benefit from the transaction. On the other hand, every rupiah a buyer saves is a rupiah lost from the sellerâs point of view. Every buyer wants a low price and every seller wants a high price. So, if fairness is good, then we should promote fairness in commercial transactions, just as we do in other areas of life. And that requires that buyer and seller at least see each other as equals.